Analisis Pengaruh Gaya Kepemimpinan, Teamwork Dan Kompensasi Dalam Meningkatkan Efektifitas Kinerja Karyawan Perusahaan Air Minum (PDAM) Kabupaten Ngawi - Mintarti Indartini; Ahadiati Rohmatiah; Henry Windrianto Darmoko (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2023)
Related to its very strategic role, the Municipal Waterworks of Ngawi District is required to have the company's performance in meeting the needs of drinking water in the community. One of them is the presence of good employee performance. This study aims to determine the partially and simultaneously influence of leadership style, teamwork and financial compensation on employee performance at the Municipal Waterworks of Ngawi District. The research population is all employees of the Municipal Waterworks of Ngawi District in 2022, totaling 288 people. The sample size was determined using the Slovin formula so that a sample of 74 employees was obtained which was determined by simple random sampling technique. The data analysis technique used the classical assumption test, multiple linear regression analysis, the coefficient of determination analysis, and hypothesis testing using the t test and F test. The results of the study are: 1) Leadership style, teamwork and financial compensation partially influences to the employee performance at the Municipal Waterworks of Ngawi District, 2) Leadership style, teamwork and financial compensation simultaneously influences to the employee performance at the Municipal Waterworks of Ngawi District.